The Comparison of Mind Mapping and Semantic Mapping to Enhance the Reading Comprehension - Musdalifah, Musdalifah (Universitas Muhammadiyah Enrekang, 2019)
This research was to prove which technique (Mind Mapping or Semantic Mapping) was effective to enhance the reading comprehension of the second graders of SMA Muhammadiyah Kalosi Enrekang regency and to prove which technique (Mind Mapping or Semantic Mapping) was effective to enhance the interests of the second graders of SMA Muhammadiyah Kalosi Enrekang regency. This research employed experimental design and cluster random sampling technique. The population of this research was the second graders of SMA Muhammadiyah Kalosi Enrekang regency in academic 2018/2019. The sample consisted of 72 students which belong to two classes; 36 students in first experimental class and 36 students in second experimental class. Research instruments were used to collect the data in this research namely reading comprehension test and questionnaire. The mean score of the students in Mind mapping technique class was 84.00 and the mean score of the students in Semantic mapping technique class was 76.97. The result of the students’ interest showed that Mind Mapping is higher than Semantic Mapping. Therefore, H1 (alternative hypothesis) of this research which said Mind Mapping is more effective than Semantic Mapping to enhance students’ reading comprehension was accepted.